Caminhos teológicos e fenomenológicos de uma igreja terapêutica - Coelho, Nivaldo Didini (2013)
In recent days, Protestant Christian churches have been marked by a desire for numerical growth as well as for subjective growth in importance, imbued with a great emphasis on personal success of the individual. The Mission of the Church as an evangelical commission has been transformed into projects which relegate the (basic) practices of caring for one s neighbor to the category of mere administrative practices which can contribute to the growth of the institution, in this way adapting to the logic of the world. When care and therapy do not have the level of objectivity required and amply witnessed to in the Gospels, both through what Jesus did and what in his divine pedagogy he taught about emptying oneself in benefit of many, it is important that we reflect on the present state of the faith communities which join in confessing Jesus as the Christ. To help in this reflection, the present dissertation seeks to analyze the possibility of developing a Therapeutic Church, through considering what the Word of God has to teach about care and therapy, as exemplified in the actions of God throughout the history of his people and continuing through the Gospels. On this basis, the dissertation seeks to contribute to the practice of care and therapy, in dialogue with Michel Henry s concept of Phenomenology of Life.